Pseudomonas aeruginosa infection liberates transmissible, cytotoxic prion amyloids. Issue 7 (17th March 2017) - Balczon, Ron; Morrow, K. Adam; Zhou, Chun; Edmonds, Bradley; Alexeyev, Mikhail; Pittet, Jean‐Francois; Wagener, Brant M.; Moser, Stephen A.; Leavesley, Silas; Zha, Xiangming; Frank, Dara W.; Stevens, Troy
ABSTRACT: Patients who recover from pneumonia subsequently have elevated rates of death after hospital discharge as a result of secondary organ damage, the causes of which are unknown. We used the bacterium Pseudomonas aeruginosa, a common cause of hospital‐acquired pneumonia, as a model for investigating this phenomenon. We show that infection of pulmonary endothelial cells by P. aeruginosa induces production and release of a cytotoxic amyloid molecule with prion characteristics, including resistance to various nucleases and proteases. This cytotoxin was self‐propagating, was neutralized by anti‐amyloid Abs, and induced death of endothelial cells and neurons. Moreover, the cytotoxin induced edema in isolated lungs. Endothelial cells and isolated lungs were protected from cytotoxin‐induced death by stimulation of signal transduction pathways that are linked to prion protein. Analysis of bronchoalveolar lavage fluid collected from human patients with P. aeruginosa pneumonia demonstrated cytotoxic activity, and lavage fluid contained amyloid molecules, including oligomeric t and Ab. Demonstration of long‐lived cytotoxic agents after Pseudomonas infection may establish a molecular link to the high rates of death as a result of end‐organ damage in the months after recovery from pneumonia, and modulation of signal transduction pathways that have been linked to prion protein may provide a mechanism for intervention.—Balczon, R., Morrow, K. A., Zhou, C., Edmonds, B., Alexeyev, M., Pittet, J.‐F., Wagener, B. M., Moser, S. A., Leavesley, S., Zha, X., Frank, D. W., Stevens, T. Pseudomonas aeruginosa infection liberates transmissible, cytotoxic prion amyloids. FASEB J. 31, 2785–2796 (2017). www.fasebj.org